Peningkatan Keterampilan Menulis Peserta Didik pada Teks Informatif Menggunakan Model Discovery Learning di Kelas III SDN 05 Birugo Kota Bukittinggi - Khomissa, Lailan; Alwi, Nur Azmi (Asian Journal of Early Childhood and Elementary Education, 2025)
Writing skills are an important aspect of Indonesian language learning, but there are still many students who have difficulty in writing informative texts well. Based on observations in class III SDN 05 Birugo Kota Bukittinggi, it was found that students experienced problems in determining the main idea, organizing the content of the text systematically, and using correct spelling and punctuation. This study aims to improve students' writing skills through the application of the Discovery Learning model. The research method used was classroom action research (PTK) with qualitative and quantitative approaches, which was carried out in two cycles. The research subjects were 20 third grade students of SDN 05 Birugo. Data were collected through writing skill tests, observations, interviews, and document analysis. The results showed that the use of the Discovery Learning model was able to significantly improve students' writing skills. In cycle I, the average score of students' writing skills was in the moderate category (C), while in cycle II it increased to the good category (B). In addition, students became more active in the learning process and were able to develop ideas in a more structured way. It is recommended for educators to apply the Discovery Learning model in learning to write so that students are more independent in exploring their ideas. Future research can develop this model with a variety of more innovative techniques to optimize learning outcomes.